Impact of KRAS G12C mutation in patients with advanced non-squamous non-small cell lung cancer treated with first-line pembrolizumab monotherapy. (December 2022) - Justeau, Grégoire; Huchot, Eric; Simonneau, Yannick; Roa, Magali; Le Treut, Jacques; Le Garff, Gwenaelle; Bylicki, Olivier; Schott, Roland; Bravard, Anne-Sophie; Tiercin, Marie; Lamy, Régine; De Chabot, Gonzague; et al.
Highlights: In 681 non-squamous aNSCLC PD-L1 ≥ 50 % patients, 12.5 % had a KRAS G12C mutation. No clinical or biological difference between KRAS G12C and KRAS non-G12C patients. KRAS G12C had no impact on first-line pembrolizumab efficacy in non-squamous aNSCLC. Abstract: Objectives: Few data are available on the impact of KRAS mutation in patients with advanced non-squamous non-small cell lung cancer (aNSCLC) treated with immunotherapy. This analysis assessed the impact of KRAS mutation on the efficiency of first-line pembrolizumab immunotherapy in aNSCLC patients with PD-L1 ≥ 50 %. Methods: This was a secondary analysis of the ESCKEYP study, a retrospective, national, multicenter study which included consecutively all metastatic NSCLC patients who initiated first-line treatment with pembrolizumab monotherapy from May 2017 (date of pembrolizumab availability in this indication in France) to November 22, 2019 (pembrolizumab-chemotherapy combination approval). Progression-free survival (PFS) and overall survival (OS) were calculated from the start of pembrolizumab treatment by the Kaplan-Meier method. Tumor response and PFS were assessed locally. Results: Among the 681 non-squamous aNSCLC PD-L1 ≥ 50 % patients treated with pembrolizumab in the first line, 227 (33.0 %) had a KRAS mutation ( KRAS G12C, 12.5 %; KRAS non-G12C, 20.5 %). Except among non-smokers ( KRAS G12C, 0 %; KRAS non-G12C, 2.9 %; no KRAS mutation, 9.2 %), patients presented no differences in terms of sex, age, number and sites of metastatic disease at diagnosis, use of corticosteroids, use of antibiotics, and for biological factors between wild-type KRAS, KRAS G12C and non- KRAS G12C groups. Median (95 % CI) PFS in months were 7.0 (3.7–14) for KRAS G12C, 4.8 (3.4–6.7) for KRAS non-G12C and 8.5 (7.3–10.6) for wild-type KRAS genotypes (p = 0.23). Median OS were 18.4 (12.6-NR), 20.6 (11.4-NR) and 27.1 (18.7–34.2) months, respectively (p = 0.57). Conclusion: No difference in efficacy was observed in non-squamous aNSCLC patients treated with first-line pembrolizumab immunotherapy whether they presented a KRAS G12C, non KRAS G12C or wild-type KRAS genotype.